The StoNED age: The Departure Into a New Era of Efficiency Analysis? A MC Study Comparing StoNED and the "Oldies" (SFA and DEA) - Mark Andor; Frederik Hesse (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Based on the seminal paper of Farrell (1957), researchers have developed several methods for measuring e fficiency. Nowadays, the most prominent representatives are nonparametric data envelopment analysis (DEA) and parametric stochastic frontier analysis (SFA), both introduced in the late 1970s. Researchers have been attempting to develop a method which combines the virtues – both nonparametric and stochastic – of these "oldies". The recently introduced stochastic non-smooth envelopment of data (StoNED) by Kuosmanen and Kortelainen (2010) is such a promising method. This paper compares the StoNED method with the two "oldies" DEA and SFA and extends the initial Monte Carlo simulation of Kuosmanen and Kortelainen (2010) in several directions. We show, among others, that, in scenarios without noise, the rivalry is still between the "oldies", while in noisy scenarios, the nonparametric StoNED PL now constitutes a promising alternative to the SFA ML.
Keywords: C14; D24; L51; 330